Some Characterization of Fermatean Fuzzy Ideals - Amal Kumar Adak; Gauri Kant Kumar (International Journal of Mathematics And its Applications, 2025)
Fermatean fuzzy sets are expanded to include intuitionistic and pythagorean fuzzy sets with extra advantage of avoiding underlying limitations. The primary objective of this study is to introduce Fermatean fuzzy ideals. The principles of level sets of Fermatean fuzzy are discussed and explore various algebraic properties associated with these sets.